2016
DOI: 10.3945/jn.116.231209
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality and Its Association with Cardiometabolic Risk Factors Vary by Hispanic and Latino Ethnic Background in the Hispanic Community Health Study/Study of Latinos

Abstract: Background: Healthful diet quality has been associated with a lower risk of metabolic syndrome (MetS) in several

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 43 publications
5
82
3
Order By: Relevance
“…Diet quality as measured by adherence to AHA recommendations was significantly associated with a healthier cardiometabolic profile and lower odds of allostatic load (8,27). When diet quality was defined with the AHEI in a separate study among Hispanic/Latino ethnic subgroups, we did not detect an association with metabolic syndrome in Puerto Ricans, although it was reported in other subgroups (28). The cross-sectional nature of both studies may affect directionality.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…Diet quality as measured by adherence to AHA recommendations was significantly associated with a healthier cardiometabolic profile and lower odds of allostatic load (8,27). When diet quality was defined with the AHEI in a separate study among Hispanic/Latino ethnic subgroups, we did not detect an association with metabolic syndrome in Puerto Ricans, although it was reported in other subgroups (28). The cross-sectional nature of both studies may affect directionality.…”
Section: Introductionmentioning
confidence: 59%
“…Higher diet quality among Hispanics with diabetes has been shown in another study (28). Thus, it is important to adjust for preexisting conditions in the association between diet and cardiometabolic markers.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Modifiable dietary lifestyle factors have been shown to contribute to post‐diagnosis survival in predominantly non‐Hispanic white populations of breast cancer survivors . Some subgroups of Hispanics/Latinos have dietary patterns low in fruits and vegetables and we and others have previously reported that Hispanics/Latinas in northern Manhattan consume diets low in fruits and vegetables and high in fat and high in saturated fat …”
Section: Introductionmentioning
confidence: 69%
“…The dietary guidelines for Americans recommend focusing on whole fruits instead of fruit juice . As legumes are commonly eaten by many Hispanic subgroups, the intervention did not focus on augmenting legume intake . Dietary intake was assessed by study interviewers at baseline, 6 and 12 months using three 24‐hour recall assessments (2 weekdays, 1 weekend day) following the multiple pass approach and using the Nutrition Data System for Research developed by the University of Minnesota (1 in‐person during the baseline clinic visit, 2 by phone) .…”
Section: Methodsmentioning
confidence: 99%